Peripheral arterial disease in Central Africa : Epidemiology, risk factors, marker prognostic - (:unkn) unknown (My University, 2014)
With the aging of the global population, the prevalence of non-communicable, including cardiovascular, diseases is increasing. While epidemiological studies on peripheral artery disease (PAD) have been mainly conducted in high-income countries, a few have been carried out in low-and middle-income countries, including in Africa. EPIDEMCA (Epidemiology of Dementia in Central Africa) is a cross-sectional population-based study in rural and urban areas of two countries of Central Africa: Central African Republic (CAR) and the Republic of Congo (ROC). Overall, its aim was to investigate the health status in aging population in Central Africa, with a special focus on cognitive disorders, PAD (Ankle-Brachial Index (ABI) ≤0.90). and cardiovascular risk factors as well as their inter-relationship. The EPIDEMCA program was carried out, among people aged 65 years and over, between 2011 and 2012. Among 2002 subjects who agreed to participate, reliable demographic and vascular data were available in 1871 subjects.Overall, the prevalence of PAD was 14.8% reachting 22.2% after the age of 80. The prevalence was higher in ROC than in CAR (17.4% vs. 12.2%, p=0.0071) and in females than males (16.6% vs. 11.9%, p=0.0122). Higher rates of PAD were found in urban area in ROC (20.7% vs. 14.4% in rural area, p=0.0114), not in CAR (11.5% vs. 12.9%, p=ns). In the multivariate analysis, PAD significantly associated factors were described: age (OR: 1.03; p=0.0039), dyslipidemia (OR: 1.88; p=0.0034), smoking (OR: 1.78; p=0.0026), and more specifically undernutrition (OR: 2.09, p=0.0009). Undernutrition was still significantly associated with PAD after adjustment to all potential confounding factors in males as well as in females (OR: 2.82, p= 0.0038 respectively OR: 1.75, p= 0.0492). As epidemiological research on the implication of atherosclerosis in the development of cognitive impairment in general population is lacking in Africa, we focused on the role of ABI as an availabl
Keywords: African Research